PENGARUH PENDIDIKAN & PELATIHAN, PRESTASI BELAJAR KEWIRAUSAHAAN TERHADAP SIKAP KEWIRAUSAHAAN PESERTA DIDIK SMK N 1 CERME - Asfiatul, Furi (Jurnal Kebijakan dan Pengembangan Pendidikan, 2013)
Furi AsfiatulAin Guru Matematika SMK N 1 Cerme Email: r12n_2004@yahoo.comAbstract:This quantitative study revealed that: 1) the students? entrepreneurship behaviors of the twelfth graders in Public Vocational School 1 Cerme was categorized very high; 2) the implementation of the entrepreneurship education and training was categorized high; 3) the learners? entrepreneurship learning achievement was categorized high; 4) the implementation of entrepreneurship education and training significantly influenced students? entrepreneurship behaviors for 31.4 %; 5) there was no correlation between learners? entrepreneurship learning achievement and entrepreneurship behaviors; 6) both the students? achievements and the entrepreneurship education and training affected the students? entrepreneurship behaviors for 8.1%; and 7) it was the entrepreneurship education which successfully improved the students? entrepreneurship behaviors at Public Vocational School 1 Cerme.Keywords: entrepreneurial attitudes, education and training, entrepreneurial learning achievementAbstrak:Penelitian ini menggunakan pendekatan kuantitatif. Hasil penelitian menunjukkan: 1) sikap kewirausahaan peserta didik kelas 12 SMK N 1 Cerme dikategorikan sangat tinggi; 2) pelaksanaan pendidikan & pelatihan kewirausahaan termasuk pada kategori tinggi; 3) prestasi belajar kewirausahaan termasuk pada kategori tinggi; 4) terdapat pengaruh pendidikan & pelatihan kewirausahaan terhadap sikap kewirausahaan sebesar 31,4%; 5) tidak terdapat pengaruh prestasi belajar kewirausahaan terhadap sikap kewirausahaan; 6) pendidikan & pelatihan dan prestasi belajar kewirausahaan secara bersama-sama mempunyai pengaruh terhadap sikap kewirausahaan peserta didik SMK N 1 Cerme, sebesar 8,1%; dan 7) pelaksanaan pendidikan & pelatihan kewirausahaan yang dapat meningkatkan sikap kewirausahaan peserta didik SMK N 1 Cerme adalah pendidikan kewirausahaan. Katakunci: sikap kewirausahaan, pendidikan & pelatihan, prestasi belajar kewirausahaan